2018
DOI: 10.12788/jhm.2910
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Conditions and Unplanned Hospital Readmissions in Children

Abstract: MHCs are associated with a higher likelihood of hospital readmission in children admitted for medical conditions and procedures. Understanding the influence of MHCs on readmissions could guide strategic planning to reduce unplanned readmissions for children with cooccurring physical and mental health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…Recent studies have shown a high growth of medical hospitalizations and costs for children with comorbid psychiatric disease, as compared to those without, 103 as well as longer hospital lengths of stay and higher rates of hospital readmission for medical illnesses in children with psychiatric disease. [104][105][106] Initial evidence suggests that psychiatric intervention may improve overall medical outcomes, health care utilization, and costs in these populations. For instance, in a recent study of pediatric admissions at a freestanding, tertiary pediatric hospital, Bujoreanu and colleagues demonstrated that earlier involvement of child psychiatric consultation led to shorter lengths of stay and lower overall hospital charges, and evidence suggests that psychiatric intervention for children with particular chronic medical conditions can lead to lower overall health care utilization.…”
Section: Funding Challenges and New Models Of Carementioning
confidence: 99%
“…Recent studies have shown a high growth of medical hospitalizations and costs for children with comorbid psychiatric disease, as compared to those without, 103 as well as longer hospital lengths of stay and higher rates of hospital readmission for medical illnesses in children with psychiatric disease. [104][105][106] Initial evidence suggests that psychiatric intervention may improve overall medical outcomes, health care utilization, and costs in these populations. For instance, in a recent study of pediatric admissions at a freestanding, tertiary pediatric hospital, Bujoreanu and colleagues demonstrated that earlier involvement of child psychiatric consultation led to shorter lengths of stay and lower overall hospital charges, and evidence suggests that psychiatric intervention for children with particular chronic medical conditions can lead to lower overall health care utilization.…”
Section: Funding Challenges and New Models Of Carementioning
confidence: 99%
“…Dies ist für die betroffenen, körperlich kranken Kinder häufig sehr herausfordernd und belastend [1,2]. Studien zeigen, dass Krankenhausaufenthalte bei Kindern zu einer generellen psychischen Belastung [3] oder sogar zu posttraumatischen Belastungssymptomen führen können [4,5].…”
Section: Introductionunclassified
“…12 Factors affecting psychiatric readmissions are not restricted to the clinical domain but are multifaceted, encompassing individual, environmental and clinical dimensions. 1,5,9,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, there is no consensus on the predictors of psychiatric readmission; for example, a large-scale cross-sectional analysis in the USA showed that length of stay is associated with risk of readmission within 30 days post-discharge. 31 However, a national case register study did not find that the length of hospital stay was an independent risk factor for readmission within 30 days, though age up to 45 years, short duration between index admission, and readmission and prior hospitalization were identified as risk factors.…”
Section: Introductionmentioning
confidence: 99%